PENYELESAIAN KDRT BERBASIS RESTORATIVE JUSTICE PADA KEPOLISIAN RESORT SINJAI PERSPEKTIF HUKUM ISLAM - Nofianggira, Rezky; Hamzah, Hamzah; Nawawi, Jumriani (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This research examines the problem of domestic violence within the Sinjai Police Department. The aim of the research is to reveal the views of Islamic law on the mechanism for resolving domestic violence using the theory of restorative justice within the Sinjai Police Department. Qualitative research method with a normative and empirical approach, supported by primary data sourced from interviews, observation and documentation. As well as, secondary data sourced from legislation, National Police Regulations, the Koran, and related literature. The research results show that: First, the mechanism for resolving domestic violence cases using a Restorative Justice approach at the Sinjai Police is through the stages of complaints/reports from the public, providing victim protection, then investigators taking statements from victims or witnesses, and conducting an investigation of the crime scene. After that a case was filed. Apart from that, investigators use mediation. If you agree to make peace, a statement letter will be made to maintain the unity of the family, and the investigation will be stopped as part of restorative justice efforts. Second, the mechanism for resolving domestic violence cases using restorative justice from an Islamic legal perspective as an effort to provide the best for perpetrators and victims in accordance with the justice they expect. Whether the decision to reconcile or divorce has also been regulated in the Koran and is in accordance with the restorative justice mechanism.